Pengaruh Ukuran Perusahaan, Good Corporate Governance, dan Kinerja Keuangan Terhadap Pengungkapan Corporate Social Responsibility - Putu Elmytia Dewi; I Putu Gede Diatmika (Universitas Pendidikan Ganesha, 2021)
This research was conducted to determine the effect of company size, managerial ownership, size of board of commissioners, institutional ownership, and financial performance on corporate CSR disclosure. Using quantitative methods with data sourced from secondary data. The banking sector as the research population is companies listed in 2016-2018 on the Indonesia Stock Exchange. A sample of 40 companies taken by purposive sampling method.